Profile of Automation of Electricity Distribution System Bhayangkara University Surabaya - Agus Kiswantono; E Nur Cahyono; Hermawan (Fakultas Teknik Universitas Bhayangkara, 2021)
Electrical Power Transmission is the process of distributing electricity from the power plant to the electricity distribution channel (substation distribution) so that it can be distributed to consumers who use electricity. Human Machine Interface (HMI) is a system that connects humans and machines. HMI can be in the form of controlling and visualizing status, either manually or through computer visualization that is real time. .Microsoft Visual Basic .NET is a tool for developing and building applications that run on top of the .NET Framework system. Arduino is a microcontroller that has been developed. Serial communication is one of the methods of data communication in which only one bit of data is transmitted over a strand of cable at a time